(untitled) (American Journal of Technology and Applied Sciences, 2025)
This article examines the integration of modern technologies and traditional artistic principles in contemporary clothing design. The study focuses on the evolution of fashion from a basic necessity to a sophisticated form of artistic expression, emphasizing the crucial synergy between art and technological production. The paper provides a detailed analysis of key modern approaches, including the use of digital technologies (3D modeling, VR, AR, AI), innovative materials (smart fabrics, nano-textiles), and the principles of sustainable fashion. A special section explores the application of these methods in the context of national heritage, using Uzbek atlas and adras fabrics as a case study for blending tradition with innovation. The article concludes that the future of fashion design lies in a holistic integration of aesthetics, digital innovation, and ecological responsibility, transforming clothing into a product of cultural, technological, and artistic synthesis.